New data to the reproduction results of Hungarian Large White breeding boars - Bene, Szabolcs; Fekete, Zsuzsanna; Lendvay, Miklós; Rajnai, Csaba; Polgár, Péter J.; Szabó, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2010)
Direct effect of breeding boars on reproduction was studied in the seedstock Large White herd of the University of Pannonia Georgikon Faculty at Keszthely. Data of 62 breeding boars mated to 430 sows resulting 1917 farrowings were evaluated.The mean values and standard deviation of the studied traits are as follows: fertility 71.2 ± 8.95%, gestation length 116 ± 2.33 day, live born piglets 10.4 ± 3.34 heads, dead born piglets 8.8 ± 15.59%, litter weight at 1st day 15.0 ± 4.73 kg, average weight at 1st day 1.5 ± 0.30 kg, mortality in the first 21 days 14.4 ± 20.20%, 21 day piglet 9.0 ± 2.72 heads, litter weight at 21st day 51.5 ± 17.62 kg, average weight at 21st day 5.5 ± 1.56 kg, weaned pig 8.7±2.8 heads. Significant differences between boars were obtained in all examined traits.The results of this study call attention to the fact that breeding boars, as sires, have a big direct effect on the reproduction performances. So, selection of good sires is very important in the course of breeding.
Keywords: Hungarian Large White; reproduction; nursing; effect of boars